Cooperative learning has its effect on developing the technical skill of students of the Department of Family Education and the technical professions in Arabic calligraphy (Al-Rakka Line) (Journal of the College of Basic Education, 2022)
Cooperative learning is a good way to address some of the problems facing students, such as parting, introverting, or being isolated from the rest of the students. , And see and develop self-knowledge, this research includes an experiment using cooperative learning, with the aim of identifying its impact in developing the technical skill of students, as the first chapter contains the research problem, its importance, the goal of research and its limits, and the definition of terms and the researcher studied in the second chapter the theoretical background of Cooperative learning, and the third chapter includes research procedures, as the researcher chose the experimental design of one sample with a pre and posttest, the research community and his sample, and the development of a teaching plan, behavioral goals, research tools, honesty and consistency, then statistical analysis of the test items, as well as preparing a form The evaluation and application of the experiment, and the fourth chapter contains the interpretation of the results, conclusions, recommendations and proposals, and then the sources used to complete the research.